NAFKAH ANAK HASIL PERNIKAHAN FASID PERSPEKTIF FIKIH SYAFI’IYAH - Aula Yazid, Nur; Al Amin, Habibi (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2024)
In the context of Islamic law, the fulfillment of child support is a primary obligation of parents as regulated by various legal sources, including the Qur'an, Hadith, and the views of both classical and contemporary scholars. However, issues arise when the child is born from an invalid marriage, known as nikah fasid. Nikah fasid refers to a marriage that does not fulfill one or more conditions and pillars required by Islamic law, rendering it null or invalid. This study is a qualitative literature review. The data in this research is analyzed descriptively. The primary sources for this study are the texts of the Shafi'i school of thought. Data were collected through documentation methods, selected, and analyzed using content analysis. The validity of the data was ensured through extensive literature review and sufficient references to enhance the credibility of the research findings. The results of the study indicate that, according to Shafi'i jurisprudence, from the perspective of the contract, an invalid marriage does not obligate the provision of financial support. However, considering the status of the child born from such a marriage, whose lineage is still attributed to the biological father, financial support must still be provided to protect the child’s rights in accordance with Islamic teachings.